Balance aparente de nutrientes (N,P,K) en dos unidades de producción ubicadas en el municipio de San Ramón, departamento de Matagalpa, durante el período 1997-1999 - Aragón Ocón, Isidro Antonio; Aráuz Úbeda, Juan Ángel (2000)
A study on a.pparent balance of nutrients was held in two farms located in the municipality of San Ramón, department of Matagalpa, to know plot management and cummt soíl fertility. The activities and managements by fimners on the fann were follow during th.tee years (1997- 1999), and were based on field books filled by the farmers, the infonnation was compiled trough periodic visits (once a week) in the two fanns and synthesizing in square oí summary. The study was started with soil samples recoilection and plants samples ftom (crops established in eacb plot) which were send to the taboratory for its respective analysis. In the samples of soil the content ofN, P, K. pH, perceot of material organic and texture were measured, in the samples ofplants was analyzed N, P, K content, to every part oí the plant (root, steam, leave and ftuit). All of that was utílized to know the inputs and outputs ofN, P, and K for every plot in order to calculate the nutrients balance. The result obtained in the fium ofCatalino Figueroa, retlecting a negative balance ofN, P, K. with elrtremely low values. This due mainly to stubble burning, outputs of nutrients from harvesting, low fertilizer a.pplication etc.; these flwtors reduce the soíl nutritional reserves. In the case of Santiaao R.uiz's fium the balance obtained it's evident that fann presenta better state offertillty than Catalino's, with a better stubble management. no burn in the plots, and an adequate mineral fertílizer application. lt only presents deficieney ofN and K. but not as low as Catalino's. Farmers don't have defined pattern on plot and stubble management; if the inadequate practices by fiumers continues without using crop relations, breaks or leguminous plants, these soils will become poor soils, fann productivity wiU be reduced, this is proved by the negative balances results. Farmers don't apply the adequate ferti1ize dose, these are not according to crop nutritional necessitles; it is inftuenced by high costs of fertílizer. The culture or fanner tradition, low credit availability as weU as the quality of fumily members that is the case of Santiaao R.uiz in whicb fumily are many chíldren's, it represents more medie and scholar education expenses, that leads to a shortened budget, which not allowed to acquire the ideal fertilizer amount.